The Normative Problem of Shame - Oakberg, Timothy James (2016)
What role should shame play in our lives? This is the normative problem of shame, and it is the focus of this dissertation. Through an examination of empirical research on shame and shame-proneness, I argue that shame should have only a very limited role in our lives. More specifically, we ought not cultivate shame, because a substantial amount of empirical literature points to the conclusion that shame-proneness is counterproductive at both an individual and a societal level. Expanding on this general answer to the normative problem of shame, I discuss in detail three proposals regarding shame from the realms of legal studies and ethics. I argue that we ought not institutionalize the use of shame penalties as legal punishments. I argue that we ought not attempt to restore shame and return to something more like a shame culture. Finally, I argue that we ought not cultivate shame as tool to promote shared responsibility